2002
DOI: 10.1046/j.1365-2915.2002.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological studies on the Anopheles minimus group of mosquitoes in southern China: taxonomic review, distribution and malaria vector status

Abstract: Abstract. Mosquitoes of the Anopheles minimus group (Diptera: Culicidae) from nine Provinces of southern China were identified morphologically and by molecular characterization, using single-strand conformation polymorphisms (SSCPs) and sequence data for the D3 region of the 28S ribosomal DNA and the mitochondrial COII locus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 13 publications
0
73
0
Order By: Relevance
“…The distribution of the minimus complex is thought to extend north-westward to Uttar Pradesh in India and southward into peninsular Malaysia (Harrison et al, 1990;Chen et al, 2002Chen et al, , 2006Harbach et al, 2007), regions that we were not able to sample in this study. Although the majority of samples here belonged to Lineage A, Lineage B had only slightly lower genetic diversity implying similar population sizes, and suggesting that we have not sampled a significant part of its range.…”
Section: Lineage Distributionmentioning
confidence: 92%
See 3 more Smart Citations
“…The distribution of the minimus complex is thought to extend north-westward to Uttar Pradesh in India and southward into peninsular Malaysia (Harrison et al, 1990;Chen et al, 2002Chen et al, , 2006Harbach et al, 2007), regions that we were not able to sample in this study. Although the majority of samples here belonged to Lineage A, Lineage B had only slightly lower genetic diversity implying similar population sizes, and suggesting that we have not sampled a significant part of its range.…”
Section: Lineage Distributionmentioning
confidence: 92%
“…Mosquitoes of the Anopheles minimus species complex (hereafter minimus complex) are widespread in hilly areas throughout the Oriental Region, extending northward to about 321 30 0 N in China, westward to Uttar Pradesh in India, southward through Thailand and into peninsular Malaysia and eastward to Taiwan and the Ryukyu archipelago of Japan (Chen et al, 2002Manguin et al, 2008). Species of the complex are regarded as important vectors of human malaria throughout their distribution (Green et al, 1990;Harrison et al, 1990;Chen et al, 2002;Garros et al, 2006) showed that A. minimus consisted of two species in western Thailand, based on a lack of heterozygotes at two enzyme loci in sympatry, and informally designated them as species A and C. Sharpe et al (1999) confirmed the presence of two species in western Thailand and established the use of the third domain (D3) of 28S ribosomal DNA as a standard for molecular identification.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anopheles mosquito observation sites and three transects for analysis. Small closed circles indicate observation sites of the Anopheles species reported in published data (Dev 1996, Chen et al 2002, Overgaard et al 2002, Singh et al 2004, Yeom et al 2005, Chen et al 2006, Rueda et al 2006. Open circles are representative observation sites ( Fig.…”
Section: Validation Of the Modelmentioning
confidence: 93%